2018
DOI: 10.1108/bij-02-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key enablers for total productive maintenance (TPM) implementation in Indian SMEs

Abstract: Purpose The purpose of this paper is to identify the key enabler for total productive maintenance (TPM) implementation in Indian small and medium enterprises (SMEs) by using graph theoretic approach (GTA). There are certain enablers for TPM implementation which helps the organization to implement it successfully. It is very essential to identify the nature and impact of these key enablers. Design/methodology/approach A large number of the enablers (27) have identified for TPM implementation in Indian SMEs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 73 publications
1
24
0
1
Order By: Relevance
“…The results presented here confirm and reinforce the findings, found in the literature, which establish a relation between the level of employee motivation during TPM implementation and results in terms of operational performance (Jain et al, 2018;Kareem & Amin, 2017;Bamber et al, 1999;Attri et al, 2013;Sharma et al, 2016). The relation between motivation and performance has been studied in other contexts related to manufacturing, with similar results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results presented here confirm and reinforce the findings, found in the literature, which establish a relation between the level of employee motivation during TPM implementation and results in terms of operational performance (Jain et al, 2018;Kareem & Amin, 2017;Bamber et al, 1999;Attri et al, 2013;Sharma et al, 2016). The relation between motivation and performance has been studied in other contexts related to manufacturing, with similar results.…”
Section: Discussionsupporting
confidence: 91%
“…A few studies focused on the importance and impact of employee motivation on TPM results. Jain et al (2018) show evidence that employee motivation, along with other human-related factors is a key enabler for TPM implementation. Kareem & Amin (2017) studied the role of psychological and ethical factors in the implementation of TPM and concluded that employee motivation and morale is an important factor to enable success.…”
Section: The Role Of Motivation In the Performance Of Workersmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to this, the main objective of TQM is to generate improved product quality in order to improve firm performance (Konecny and Thun, 2011). TQM is a manufacturing program that aims at managing the entire organization in a way that excels on all dimensions of product and services that are important to customers (Chase, et al, 2014;Mehta, et al, 2019), whereas, TPM is a maintenance management program, that focuses on improving the overall equipment effectiveness by eliminating the waste, through effective participation of workforce (Nakajima, 1988;Ahuja and Khamba, 2008;Jain, et al, 2018). Each of these operational (functional) strategies incorporates a methodology, philosophy, tools/techniques to help organizations ameliorate their business results (Raval and Kant, 2017;Sahoo and Yadav, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It also supports the practices under lean umbrella such as, Just in Time, Total Quality Management and TPM. It is important in the evolution of world manufacturing for giving a new evolution in maintenance system and product quality (Jain, Singh, & Bhatti, 2018). TPM provide a new view on the maintenance especially on the quality of the organization (Rukijkanpanich & Pasuk, 2018).…”
Section: Introductionmentioning
confidence: 99%